Vitamin D Level Status and Hypertension among Elderly Iraqi People in Al Hillah City (Medico Legal Update, 2020)
Background: Vitamin D has different biological actions in the body . Vitamin D has the pleiotropic effectsin multiple organ systems, and vitamin D deficiency was suggested to be associated with high bloodpressure according to previous reports. Several interventional studies have examined the effect of vitamin Dsupplementation on high blood pressure patientsObjective: To identify Vitamin D level and its correlate with hypertension among old adult in Hilla city –Babylon province.